Multi-drug Resistant Bacteria Isolated from Pus and Phenotypic Detection of Metallo β-lactamase Activity of Pseudomonas Aeruginosa - Paudel, Pratiksha; Shrestha, Sunita; Poudel, Sushmita; Tiwari, Bishnu Raj (Nepal Journal of Health Sciences, 2021)
Introduction: Pus is an exudate, present at the site of inflammation occurring during bacterial, viral or fungal infection and is formed by pyogenic bacteria. Objective: To study the multi-drug resistant bacteria including phenotypic detection of MβL activity of Pseudomonas aeruginosa in pus isolates. Methods: This was hospital based cross-sectional study in which 179 samples of pus was collected from any site of the body either by using swab or aspirated by using syringe and cultured in respective hospitals. Thus, obtained isolates were preserved and were transported to the laboratory for further processing. Results: Out of 162 pus isolated, 67(42.0%) were Methecillin resistant Staphylococcus aureus (MRSA), 14(8%) were Methicillin sensitive Staphylococcus aureus (MSSA), 21(13.0%) were Klebsiella spp, 19(11.7%) were Escherichia coli, 14 (8.6%) were Pseudomonas aeruginosa, 10(6.2%) were Acinetobacter spp, 5(3.1%) were Streptococcus spp, 4(2.5%) were Enterococci ,3(1.9%) were Enterobacter spp, 2(1.2%) were Coagulase negative S. aureus, 1(0.6%) were Proteus vulgaris, and1(0.6%) were Citrobacter spp. Antibiogram of Gram positive cocci revealed that they showed susceptibility towards vancomycin, clindamycin, gentamycin, amikacin. Similarly, Gram negative bacilli showed good response towards gentamycin, amikacin, nitrofurantoin, colistin. Out of 162 isolates, 102(62.96%) were Multi-Drug Resistant (MDR) and 60 (37.04%) were Non-MDR. Out of 14 (8.6%) Pseudomonas aeruginosa isolates, 8(57.1%) were Imepenem resistant and among imepenem resistant, only 3(37.5%) of them showed MβL production activity. Conclusion: This study showed that Gram negative bacteria were highly resistant to antibiotics. Staphylococcus aureus was found to be more predominant bacteria in forming pus. Antibiotics used in the infections related to pus are being more resistant.